2006
DOI: 10.1038/sj.jes.7500500
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and occupational exposures and serum PCB concentrations and patterns among Mohawk men at Akwesasne

Abstract: A study was conducted to address the question of how fish consumption, occupation, and outdoor air affected serum PCB concentrations and congener patterns among 139 Native American men living near three hazardous waste sites. They were interviewed about their residential, occupational, and dietary histories, and donated 20 ml of venous blood for congener-specific PCB analysis. The similarity in the congener pattern between that found in the serum and that detected in local environmental samples was measured by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 35 publications
1
15
0
1
Order By: Relevance
“…Values less than the detection limit were set to the lowest positive value for a given analyte. This decision was based on the fact that many chemists and statisticians believe that a reported result, even if it is below the ''criterion for detection,'' is the best available estimate of the true value, and is preferable to assigning a zero or an arbitrary constant, such as one-half the detection limit (Wolff et al, 2008;Fitzgerald et al, 2007b). Coefficients of variation (SD/mean) of DDE and PCBs from the fortified pools were 10% to 15%.…”
Section: Serum Pcb Analysismentioning
confidence: 99%
“…Values less than the detection limit were set to the lowest positive value for a given analyte. This decision was based on the fact that many chemists and statisticians believe that a reported result, even if it is below the ''criterion for detection,'' is the best available estimate of the true value, and is preferable to assigning a zero or an arbitrary constant, such as one-half the detection limit (Wolff et al, 2008;Fitzgerald et al, 2007b). Coefficients of variation (SD/mean) of DDE and PCBs from the fortified pools were 10% to 15%.…”
Section: Serum Pcb Analysismentioning
confidence: 99%
“…One possible route is from other fish, such as commercial fish, yet very few of those not eating the local fish reported commercial fish consumption. Other sources of exposure are occupation [Fitzgerald et al, 2006;Prince et al, 2006] and, possibly, proximity to hazardous waste sites [Stehr-Green et al, 1988;Orloff et al, 2003;DeCaprio et al, 2005]. Of the 18 anglers that reported not eating the local catch, 12 were not currently working.…”
Section: Discussionmentioning
confidence: 98%
“…[11,12] Some evidences have shown that inhalation uptake is also a significant source route of PCBs exposure. [13,14] Results of daily intake estimation for e-waste recycling workers indicate that air inhalation contributes a large portion of low-chlorinated PCB intake (>80% for triCBs). [15] In urban areas, inhalation of indoor dust and air has been highlighted as an important pathway of PCBs exposure.…”
Section: Introductionmentioning
confidence: 99%